A study to assess the perceptions of first year medical students for choosing medical school as a career - Tiwari, Ranjana; Jain, Vikas; Arya, Rajkumar; Dwivedi, Shatkratu; Shrivastava, Divyajyoti; Tiwari, Sakshi (International Journal of Research in Medical Sciences, 2017)
Background: There are more than 44000 seats in over 350 medical colleges in India for pursuing the MBBS course. Yet medicine is not among the top vocation in most career advisories and the best school students do not aspire to be doctors. Methods: The present study was a cross sectional study done on 150 students of first semester of GR Medical College, Gwalior, Madhya Pradesh, India on a predesigned or pre validated questionnaire. Only 104 students participated in the study. Results: A total of 104 students participated in the study. Among them, 68 (65.39%) were males and 36 (34.61%) females. The maximum percentage of students was of the age group of 20 years i.e. 26 (25%). The choice of a career in the medical field is a complex personal decision influenced by a multitude of factors. Career choices are influenced by both graduates inclination before starting medical school as well as any exposure during training in medical school. Conclusions: These data showed that the maximum percentages of the Medical Students were satisfied with the medical school as 95 (91.34%) but still some of them have regrets. In choosing medical school they wants to help poor, earn money and personal development, and influenced by some doctor relative. These were important factors for decision making in medical school.